Upaya Badan Keamanan Laut dalam Menanggulangi Terjadinya Illegal Fishing - Pratama Putri, Rizka Septia; Neri Widya Ramailis (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the efforts of the Indonesian Maritime Security Agency (Bakamla) in combating illegal fishing practices in the North Natuna Sea. The research method used is a descriptive qualitative approach with a case study design at the Natuna Bakamla Station. The results of the study indicate that Bakamla carries out efforts to combat illegal fishing through a preventive and participatory approach, and plays an indirect role in the penal aspect. These efforts include routine sea patrols, the use of maritime monitoring technology, cross-agency coordination, and the involvement of coastal communities through the Indonesian Sea Guard Volunteers (RAPALA). However, the effectiveness of Bakamla's task implementation still faces obstacles such as limited human resources, fleet, budget, and overlapping authority between maritime law enforcement agencies. The conclusion of this study shows that Bakamla's role in combating illegal fishing in the North Natuna Sea has been running quite optimally as the vanguard of non-military maritime security, but requires institutional strengthening, increased coordination between agencies, and more comprehensive policy support to realize effective and sustainable maritime surveillance. Keywords: Illegal fishing, Maritime Security Agency, North Natuna Sea.